An Empirical Model of the Sporadic E Layer Intensity Based on COSMIC Radio Occultation Observations - Jun Niu; Han‐xian Fang (Space Weather)
Abstract Ionospheric sporadic E layers are common phenomena occurring in the ionospheric E region altitude (∼90–120 km) with much higher electron density. The lack of a large amount of sporadic E layer intensity observation on a global scale restrains the construction of global modeling of sporadic E layer intensity. Recent studies reveal that radio occultation observation can be used for sporadic E layer intensity inversion. In this paper, a low‐mid latitude empirical model of sporadic E layer critical frequency is constructed based on Constellation Observing System for Meteorology, Ionosphere, and Climate radio occultation data during 2007–2012. Model results show good accordance with ionosonde observations over 16 stations in different latitudes. In general, the model has a good performance in simulating the climate variation features of sporadic E layer intensity with averaged deviation 0.23 MHz which indicates a slight overestimation. Besides, spatial and temporal variations simulated by the model are also analyzed and show good agreement with known sporadic E layer features. However, the empirical may be only suitable for climate research at present and potential methods to improve the model will be investigated in the latter research.